Investigation of the Effect of Clot Deposition on the Risk of Abdominal Aortic Aneurysm Rupture by Engineering Methods - Salman, Hüseyin Enes (Fırat University, 2023)
Abdominal aortic aneurysm (AAA) is a cardiovascular disease caused by enlargement of the abdominal aorta. Untreated AAA structures continue to grow and pose a risk of rupture. AAA rupture is a health emergency, with more than half of ruptures resulting in death. Therefore, it is important to be able to diagnose AAA structures at an early stage. When there is a high level of enlargement, clot structures can form within the AAA. In this study, the effect of clot structures on the risk of AAA rupture is examined. For this purpose, an idealized AAA model is created. The AAA model is investigated by performing computational fluid dynamics (CFD) analysis considering the fluid-structure interaction. As a result, different hemodynamic conditions occurred for the cases with and without clots. AAA formation reduced the mechanical stresses on the vessel wall. The vascular stresses on the AAA wall are 12% lower for the models with high levels of clot. The results obtained contributed to the understanding of the effect of clot structures on AAA hemodynamics and mechanical stresses on the AAA wall.

Abdominal aort anevrizması (AAA) karın bölgesinde yer alan aort damarının genişlemesine bağlı olarak oluşan bir kardiyovasküler hastalıktır. Tedavi edilmeyen AAA yapıları büyümeye devam etmekte ve yırtılma riski oluşturmaktadır. AAA yırtılması acil bir sağlık durumu olup, yırtılma vakalarının yarıdan fazlası ölümle sonuçlanmaktadır. Bu nedenle erken safhada AAA yapılarını teşhis edebilmek önem teşkil etmektedir. Yüksek seviyede genişleme olduğunda AAA içinde pıhtı yapıları oluşabilmektedir. Bu çalışmada, AAA içindeki pıhtı yapılarının yırtılma riski üzerindeki etkisi irdelenmiştir. Bu amaçla idealize edilmiş bir AAA modeli oluşturulmuştur. AAA modeli katı-sıvı etkileşimi göz önüne alınarak hesaplamalı akışkanlar dinamiği (HAD) analizleri ile incelenmiştir. Gerçekleştirilen analizler sonucunda pıhtı olan ve olmayan durumlar için farklı hemodinamik koşulların oluştuğu gözlenmiştir. AAA oluşumunun damar duvarı üzerinde oluşan mekanik gerilmeleri azalttığı görülmüştür. Yüksek seviyede pıhtı içeren AAA modelinin damar gerilme seviyeleri, pıhtı içermeyen AAA modeline kıyasla %12 daha düşüktür. Elde edilen sonuçlar, pıhtı yapılarının AAA hemodinamiğine ve damar duvarındaki mekanik gerilmelere olan etkisinin anlaşılmasına katkı sağlamıştır.
Pıhtı Birikiminin Abdominal Aort Anevrizması Yırtılma Riskine Etkisinin Mühendislik Yöntemleriyle İncelenmesi
Keywords: Biomechanic; Biyomekanik